2010
DOI: 10.1111/j.1440-1746.2009.06172.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transpapillary drainage for external fistulas developing after surgical or radiological pancreatic interventions

Abstract: External pancreatic fistulas developing following percutaneous drainage of pancreatic fluid collections or surgical necrosectomy can be effectively treated by transpapillary nasopancreatic drain placement especially when there is partial ductal disruption and the disruption can be bridged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…In conclusion, the results of the study reported by Rana and colleagues in this issue of Journal of Gastroenterology and Hepatology is encouraging; 13 it confirms that endoscopic treatment of patients with EPF can often avoid an aggressive surgical approach and could be useful as a first‐line therapy when conservative treatment is unsuccessful. Precise knowledge of pancreatic duct anatomy is mandatory to ensure technical success, and this procedure should be performed by an expert.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In conclusion, the results of the study reported by Rana and colleagues in this issue of Journal of Gastroenterology and Hepatology is encouraging; 13 it confirms that endoscopic treatment of patients with EPF can often avoid an aggressive surgical approach and could be useful as a first‐line therapy when conservative treatment is unsuccessful. Precise knowledge of pancreatic duct anatomy is mandatory to ensure technical success, and this procedure should be performed by an expert.…”
mentioning
confidence: 55%
“…In this issue of Journal of Gastroenterology and Hepatology , Rana et al 13 . report their interesting experience of 12 years of EPF treatment.…”
mentioning
confidence: 99%
“…In our earlier studies also, we have noted that some of the patients with complete disruption had also the resolution of the pseudocysts/ fistulae after non-bridging transpapillary drainage although the results were not as spectacular as were noted in patients with partial disruption. 8,9,14,17 Another large study by Varadarajulu et al also reported successful resolution after transpapillary drainage in 26% (6/23) of patients with complete disruption. 18 The reason for resolution of pseudocysts in this situation is not clear, and further studies are needed.…”
Section: Discussionmentioning
confidence: 90%
“…In recent years, endoscopic treatment has proven to be an effective alternative to surgical techniques for pancreatic duct disruption [2]. Currently, the standard treatment for colonic perforation is open surgical repair.…”
Section: Introductionmentioning
confidence: 99%